Принципи створення інтелектуального інтерфейсу для розв’язування систем лінійних алгебраїчних рівнянь на комп’ютерах гібридної архітектури - HImIch, O.M.; Chistyakova, T.V.; Baranov, A.Yu. (Інститут програмних систем НАН України, 2015)
Methodology of intelligent software development for automatic researching and solving systems of linear algebraic equations on parallel hybrid computer, which combine computations on multicore computers with MIMD-architecture with accelerated computations on GPU with SIMD-architecture, is considered in this paper.